Synergistic Effects of Polyphenols and Methylxanthines with Leucine on AMPK/Sirtuin-Mediated Metabolism in Muscle Cells and Adipocytes - Bruckbauer, Antje; Zemel, Michael B. (PLOS ONE, 2014)
The AMPK-Sirt1 pathway is an important regulator of energy metabolism and therefore a potential target for prevention and therapy of metabolic diseases. We recently demonstrated leucine and its metabolite β-hydroxy-β-methylbutyrate (HMB) to synergize with low-dose resveratrol (200 nM) to activate sirtuin signaling and stimulate energy metabolism. Here we show that leucine exerts a direct effect on Sirt1 kinetics, reducing its Km for NAD+ by >50% and enabling low doses of resveratrol to further activate the enzyme (p = 0.012). To test which structure elements of resveratrol are necessary for synergy, we assessed potential synergy of structurally similar and dissimilar polyphenols as well as other compounds converging on the same pathways with leucine using fatty acid oxidation (FAO) as screening tool. Dose-response curves for FAO were constructed and the highest non-effective dose (typically 1–10 nM) was used with either leucine (0.5 mM) or HMB (5 µM) to treat adipocytes and myotubes for 24 h. Significant synergy was detected for stilbenes with FAO increase in adipocytes by 60–70% (p<0.05) and in myotubes >2000% (p<0.01). Sirt1 and AMPK activities were stimulated by ∼65% (p<0.001) and ∼50% (p<0.03), respectively. Similarly, hydroxycinnamic acids and derivatives (chlorogenic, cinnamic, and ferulic acids) combined with leucine/HMB increased FAO (300–1300%, p<0.01), AMPK activity (50–150%, p<0.01), and Sirt1 activity (∼70%, p<0.001). In contrast, more complex polyphenol structures, such as ellagic acid and epigallocatechin gallate required higher concentrations (>1 µM) and exhibited little or no synergy. Thus, the six-carbon ring structure bound to a carboxylic group seems to be a necessary element for leucine/HMB synergy with other stilbenes and hydroxycinnamic acids to stimulate AMPK/Sirt1 dependent FAO; these effects occur at concentrations that produce no independent effects and are readily achievable via oral administration.